Aeronautic giants of the new millennium : strategic competitiveness of five major players. - Soh, Carine Geok Khim. (2008)
The report provides an overview of the industrial structure and dynamics of the airline industry. It analyses the competitive strategies and financial performance of 5 airlines, namely Singapore Airlines, Cathay Pacific, British Airways, Scandinavian Airline Systems and Qantas Airways. Finally, recommendations on how each airline should position itself were given.